Betaine (TMG) as a Dietary Supplement in Sports – Mechanisms of Action, Ergogenic Effects, and Safety of Use - Tomaszek, Michał; Benecka, Agnieszka; Chojniak, Alicja Katarzyna; Kuna, Paweł Jan; Kuna, Wojciech; Chmielowiec, Laura; Radziwon, Maja; Adasiewicz, Julia; Kwaterska, Katarzyna; Borowski, Konrad (Quality in Sport, 2025)
Betaine supplementation is gaining popularity as a strategy to enhance physical performance, particularly in strength and endurance training. Although large-scale, multicenter studies remain limited, available evidence suggests potential ergogenic benefits such as improved lower-body strength and jump performance. Supplementation may also influence hormonal balance by increasing the testosterone-to-cortisol ratio, promoting an anabolic state. Findings regarding betaine’s impact on body composition remain mixed—some studies report no significant changes in lean mass or fat mass, while others suggest a reduction in fat mass without changes in overall body weight. The proposed mechanisms include increased intramuscular betaine concentration and osmotic activity, which may support recovery and protect muscle cells. Despite promising results, further well-designed clinical trials are needed to evaluate different populations, dosing protocols, and the long-term safety of supplementation. This review synthesizes the current body of knowledge and offers recommendations for future research and practical applications of betaine in sports.